2016
DOI: 10.17116/oftalma2016132435-42
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of diffuse diabetic macular edema treatment in relation to structural changes in macular region

Abstract: The effectiveness of intravitreal ranibizumab therapy for diffuse DME depends on the morphological type of macular edema by OCT. Moreover, it correlates with diabetes duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Several studies have investigated approaches for predicting DME treatment outcomes after IVI anti-VEGF therapy and report that an important factor is visual acuity at baseline [7,20,30,31,32,33]. Our study using machine learning also found that baseline visual acuity had a significant role in predicting outcomes at three different time points.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Several studies have investigated approaches for predicting DME treatment outcomes after IVI anti-VEGF therapy and report that an important factor is visual acuity at baseline [7,20,30,31,32,33]. Our study using machine learning also found that baseline visual acuity had a significant role in predicting outcomes at three different time points.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast to previous reports, we did not find that baseline OCT parameters influenced visual outcomes. This difference is likely because we only included baseline OCT measurements in our models, while prior studies also included follow-up OCT measurements [30,32,36,37].…”
Section: Discussionmentioning
confidence: 99%